2016
DOI: 10.1155/2016/4216285
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of French Marigold (Tagetes patula L.) Flowers Protect Jurkat T‐Cells against Oxidative Stress

Abstract: The flowers of French marigold (Tagetes patula L.) are widely used in folk medicine, in particular for treating inflammation-related disorders. However, cellular mechanisms of this activity demand further investigation. In the present work, we studied the potential of T. patula compounds to alleviate the oxidative stress in hydrogen peroxide-challenged human lymphoblastoid Jurkat T-cells. Crude extracts of marigold flowers and purified fractions containing flavonoids patuletin, quercetagetin, and quercetin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 35 publications
(44 reference statements)
1
20
0
Order By: Relevance
“…T. patula essential oil from Aragua state, Venezuela has been reported to contained βterthienyl (43.1%), pentatriacontane (23.9%) and 2-hexyl-1-decanol (7.8%) as major components (Romagnoli, 2005). Piperitone (33.77%), trans-β-ocimene (14.83%) and terpinolene (13.87%) were reported as major constituents in the essential oil from aerial parts of T. patula grown in Venezuela (Rondon, 2006 of leaf and flower essential oil of T. patula from Gurugram Haryana, India showed that limonene (12.9%) and piperitone (11.9%) as predominant compounds in leaf essential oils and trans-sesquisabinene hydrate (12.5%), pcymen-8-ol (11.0%) and piperitone (10.6%) in the flower essential oil (Chkhikvishvili, 2016). From Northwest Iran, hydrodistilled volatile seed oil composition of commonly growing ornamental T. patula was analyzed for its constituents by GC/MS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…T. patula essential oil from Aragua state, Venezuela has been reported to contained βterthienyl (43.1%), pentatriacontane (23.9%) and 2-hexyl-1-decanol (7.8%) as major components (Romagnoli, 2005). Piperitone (33.77%), trans-β-ocimene (14.83%) and terpinolene (13.87%) were reported as major constituents in the essential oil from aerial parts of T. patula grown in Venezuela (Rondon, 2006 of leaf and flower essential oil of T. patula from Gurugram Haryana, India showed that limonene (12.9%) and piperitone (11.9%) as predominant compounds in leaf essential oils and trans-sesquisabinene hydrate (12.5%), pcymen-8-ol (11.0%) and piperitone (10.6%) in the flower essential oil (Chkhikvishvili, 2016). From Northwest Iran, hydrodistilled volatile seed oil composition of commonly growing ornamental T. patula was analyzed for its constituents by GC/MS.…”
Section: Resultsmentioning
confidence: 99%
“…Commercially, Tagetes essential oil is produced from T. patula and T. minuta in some countries such as France, Australia and Kenya and also produced in India to a small extent (Adams, 2017). It is commercially cultivated in India as a floriculture crop (Bhattacharyya, 2010;Chkhikvishvili, 2016). The plant is herbaceous, branched, glabrous, annual and bushy.…”
Section: Introductionmentioning
confidence: 99%
“…The high anti-ischemic and antihypoxic activity of the studied extracts may be related to their rich chemical composition. So in extracts from Tagetes patula L., patuletin, patuletrin, luteolin, sesquiterpene lactones with an extensive spectrum of pharmacological activity are found includes antioxidant, anti-inflammatory, anti-cancer and cytoprotective properties (Chkhikvishvili et al, 2016). In the extract obtained from Gaillardia pulchella Foug, the main biologic active substances are represented by vicenin-2, vitexin, luteolin, apigeninone and 6-methoxylyl-tetolin, exhibiting antioxidant, anti-inflammatory and hepatoprotective activity (Moharram et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin, 6-hydroxykaempferol (50 μg/mL) obtained from Tagetes erecta L. exhibited significant anticancer activity against A549 and HEPG2 cells whereas, protocatechuic acid and quercetagetin were effective against A549 cells [75]. Crude extracts containing different flavonoid fractions and the flavonoid fraction rich in quercetin and quercetagetin possessed maximum cytoprotective activity and patuletin at high dose can exert cytotoxic effect on Jurkart cells [76]. Chemical nature of the compound and its concentration is important in deciding its cytoprotective and cytotoxic activity.…”
Section: Anti Cancer/anti Tumormentioning
confidence: 99%